Co-application of biochar and compost enhanced soil carbon sequestration in urban green space - Wang, Ben; Li, Wenfang; Xue, Na; Xi, Ruyang; Wang, Yanjun; Fang, Lele; Wang, Qiang; Liang, Xinchun; Xiao, Yiqian; Yang, Xiuyun; Wu, Xiaogang (Frontiers in Microbiology, 2025)
The mechanism of biochar and compost as soil amendments in urban green spaces remains unclear. Using Euonymus kiautschovicus as a model system, this study established eight treatment gradients, 0 (CK), single biochar applications: 4% (BC4), 8% (BC8), 12% (BC12), 7.5% compost (COM), and their combinations BCC4 (BC4 + 7.5% COM), BCC8 (BC8 + 7.5% COM), BCC12 (BC12 + 7.5% COM). Through metagenomic sequencing and metagenome-assembled genomes (MAGs) analysis, we investigated soil microbiome structure, carbon sequestration functional genes, and their interactions in response to amendments. The combined application of medium-low dose biochar (4–8%) with compost significantly optimized the physicochemical properties and microbial functions in soils. Compared to single amendments, hybrid treatments synergistically enhanced soil moisture content. Specifically, BCC8 increased by 27% compared to the CK, organic carbon levels reached 12.8 g/kg with BCC12, and available nutrients showed 45% higher available phosphorus with BCC4. Metagenomic analysis revealed that hybrid treatments reshaped microbial community structure, with BCC8 significantly enriching Acidobacteria (8.72%) and Nitrospira (1.42%), driving an increased abundance of carbon fixation genes. Among key carbon fixation pathways, the reductive tricarboxylic acid cycle (rTCA) exhibited the highest gene abundance (mean 15.03), dominated by MAG176. The Calvin-Benson-Bassham (CBB) cycle displayed broad adaptability, with MAG59 identified as a core carbon-fixing strain. This study has significant implications for the application of biochar-compost combinations in carbon management of urban green spaces.